Appropriate choice of stress modality in patients undergoing myocardial perfusion scintigraphy with a cardiac camera equipped with solid-state detectors: the role of diabetes mellitus. (11th December 2017) - Gimelli, Alessia; Liga, Riccardo; Clemente, Alberto; Pasanisi, Emilio Maria; Favilli, Brunella; Marzullo, Paolo
Abstract: Aims: To evaluate the impact of diabetes mellitus (DM) on the accuracy of myocardial perfusion scintigraphy (MPS) in detecting coronary artery disease (CAD). Methods and results: Two hundred and sixteen patients with DM and 432 matched controls were submitted to MPS on a dedicated cardiac camera equipped with cadmium–zinc–telluride (CZT) detectors and coronary angiography. Exercise stress was performed in 442 (68%) patients, while the remainders underwent vasodilator stress. Exercise level was determined as the percentage of the predicted maximal workload that was attained (%Wattmax ). The summed difference score was derived from CZT images. A coronary stenosis >70% was considered obstructive. The prevalence of obstructive CAD was 59.7% in patients with DM and 56.2% in controls ( P = NS). The accuracy of MPS in detecting CAD was similar in patients with and without DM [area under the ROC curve (AUC) 0.77 vs. 0.78, P = NS]. An interaction between the accuracy of MPS and cardiac stress-protocol was revealed. In fact, in patients with DM exercise stress CZT had a lower accuracy than vasodilator-stress (AUC 0.70 vs. 0.89, P < 0.001), because of a lower specificity (45% vs. 69%), while in the control group the accuracy of MPS was similar regardless of the stress-protocol adopted. Patients with DM attained a significantly lower %Wattmax during exercise than controls (76 ± 27% vs. 82 ± 26%, P = 0.038), which resulted an independent predictor of reduced specificity ( P = 0.026). Conclusion: The accuracy of CZT imaging in patients with DM is elevated, and it is quite comparable to the one obtained in patients without DM. However, a reduced specificity can be expected in the case of exercise stress CZT, because of an impaired exercise capacity.